Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure! Let's begin by rewriting the given equation [tex]\(x^2 + 2x + y^2 - 8y + 1 = 0\)[/tex] into its graphing form, which is typically the standard form of a circle or an ellipse.
First, we need to complete the square for the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
### Step 1: Complete the Square
For the [tex]\(x\)[/tex] terms:
The given terms involving [tex]\(x\)[/tex] are [tex]\(x^2 + 2x\)[/tex]. To complete the square:
1. Take the coefficient of [tex]\(x\)[/tex] which is [tex]\(2\)[/tex], divide it by 2: [tex]\(\frac{2}{2} = 1\)[/tex].
2. Square the result: [tex]\(1^2 = 1\)[/tex].
So, we add and subtract [tex]\(1\)[/tex] to complete the square:
[tex]\[x^2 + 2x = (x + 1)^2 - 1.\][/tex]
For the [tex]\(y\)[/tex] terms:
The given terms involving [tex]\(y\)[/tex] are [tex]\(y^2 - 8y\)[/tex]. To complete the square:
1. Take the coefficient of [tex]\(y\)[/tex] which is [tex]\(-8\)[/tex], divide it by 2: [tex]\(\frac{-8}{2} = -4\)[/tex].
2. Square the result: [tex]\((-4)^2 = 16\)[/tex].
So, we add and subtract [tex]\(16\)[/tex] to complete the square:
[tex]\[y^2 - 8y = (y - 4)^2 - 16.\][/tex]
### Step 2: Substitute Back into the Original Equation
We substitute these completed squares back into the original equation:
[tex]\[x^2 + 2x + y^2 - 8y + 1 = 0\][/tex]
Rewriting gives us:
[tex]\[(x + 1)^2 - 1 + (y - 4)^2 - 16 + 1 = 0.\][/tex]
### Step 3: Simplify the Equation
Now we simplify the equation:
[tex]\[(x + 1)^2 - 1 + (y - 4)^2 - 16 + 1 = 0\][/tex]
[tex]\[(x + 1)^2 - 16 + (y - 4)^2 = 0\][/tex]
[tex]\[(x + 1)^2 + (y - 4)^2 - 16 = 0\][/tex]
[tex]\[(x + 1)^2 + (y - 4)^2 = 16\][/tex]
This final equation [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex] represents a circle with center [tex]\((-1, 4)\)[/tex] and radius [tex]\(\sqrt{16} = 4\)[/tex].
### Step 4: Compare with Given Options
Comparing this with the given options:
a. [tex]\((x - 3)^2 + (y - 2)^2 = 1\)[/tex]
b. [tex]\((x - 2)^2 + (y + 5)^2 = 11\)[/tex]
c. [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex]
d. [tex]\((x + 2)^2 + (y - 1)^2 = 9\)[/tex]
The correct match is:
c. [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex].
Thus, the correct answer is option c.
First, we need to complete the square for the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
### Step 1: Complete the Square
For the [tex]\(x\)[/tex] terms:
The given terms involving [tex]\(x\)[/tex] are [tex]\(x^2 + 2x\)[/tex]. To complete the square:
1. Take the coefficient of [tex]\(x\)[/tex] which is [tex]\(2\)[/tex], divide it by 2: [tex]\(\frac{2}{2} = 1\)[/tex].
2. Square the result: [tex]\(1^2 = 1\)[/tex].
So, we add and subtract [tex]\(1\)[/tex] to complete the square:
[tex]\[x^2 + 2x = (x + 1)^2 - 1.\][/tex]
For the [tex]\(y\)[/tex] terms:
The given terms involving [tex]\(y\)[/tex] are [tex]\(y^2 - 8y\)[/tex]. To complete the square:
1. Take the coefficient of [tex]\(y\)[/tex] which is [tex]\(-8\)[/tex], divide it by 2: [tex]\(\frac{-8}{2} = -4\)[/tex].
2. Square the result: [tex]\((-4)^2 = 16\)[/tex].
So, we add and subtract [tex]\(16\)[/tex] to complete the square:
[tex]\[y^2 - 8y = (y - 4)^2 - 16.\][/tex]
### Step 2: Substitute Back into the Original Equation
We substitute these completed squares back into the original equation:
[tex]\[x^2 + 2x + y^2 - 8y + 1 = 0\][/tex]
Rewriting gives us:
[tex]\[(x + 1)^2 - 1 + (y - 4)^2 - 16 + 1 = 0.\][/tex]
### Step 3: Simplify the Equation
Now we simplify the equation:
[tex]\[(x + 1)^2 - 1 + (y - 4)^2 - 16 + 1 = 0\][/tex]
[tex]\[(x + 1)^2 - 16 + (y - 4)^2 = 0\][/tex]
[tex]\[(x + 1)^2 + (y - 4)^2 - 16 = 0\][/tex]
[tex]\[(x + 1)^2 + (y - 4)^2 = 16\][/tex]
This final equation [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex] represents a circle with center [tex]\((-1, 4)\)[/tex] and radius [tex]\(\sqrt{16} = 4\)[/tex].
### Step 4: Compare with Given Options
Comparing this with the given options:
a. [tex]\((x - 3)^2 + (y - 2)^2 = 1\)[/tex]
b. [tex]\((x - 2)^2 + (y + 5)^2 = 11\)[/tex]
c. [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex]
d. [tex]\((x + 2)^2 + (y - 1)^2 = 9\)[/tex]
The correct match is:
c. [tex]\((x + 1)^2 + (y - 4)^2 = 16\)[/tex].
Thus, the correct answer is option c.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.